Strategic analysis of water institutions in India: application of a new research paradigm - Saleth, Rathinasamy Maria (International Water Management Institute, 2004)
The overall objective of this paper is to outline the analytical framework and theoretical approach underlying a new research paradigm and illustrate how this paradigm can be used for the strategic analysis of water institutions by applying it to the Indian context.